The Effect Of Innovation And Government Subsidies On Financing Constraints Of Agricultural Small And Medium-Sized Enterprises In China: The Interaction Effect Of Digital Finance - Huang, Siqi (2024)
The agricultural sector is crucial for achieving many of the 17 Sustainable Development Goals (SDGs) of the United Nations. While impressive agricultural production has been achieved, China still needs to transform the agricultural sector to be more sustainable, which requires the agricultural Small and Medium-sized Enterprises (SMEs) to play an essential role. However, the problem of financing constraints limits the effect of agricultural SMEs. Meanwhile, firm innovation, which is important for agricultural sustainability transformation, is likely to exacerbate financing difficulties. Therefore, as the primary objective, this study investigates the impact of innovation on financing constraints using 186 agricultural enterprises that are listed in the New Third Board of China (also known as NEEQs) from 2011 to 2021. Using GMM estimation, the results show that innovation helps to alleviate the financing constraints of agricultural SMEs. Furthermore, heterogeneous analysis on the effects of different types of innovation indicates that the invention patent, compared with non-patent, is more effective in alleviating financing constraints. In supporting agricultural development, the Chinese government has granted subsidies for eligible enterprises.